2014
DOI: 10.4037/ajcc2014292
|View full text |Cite
|
Sign up to set email alerts
|

Pepsin and Amylase in Oral and Tracheal Secretions: A Pilot Study

Abstract: worth, RN, MSN, CCRN, CCNS, and Devendra Indulal Mehta, MBBS, MSc(dist), MRCP Background Endotracheal intubation increases the risk for microaspiration of secretions around the tube cuff. Pepsin has been used as a biomarker for gastric aspiration. Amylase is a newer proposed biomarker for aspiration of oral contents. Objective To assess the presence of pepsin and amylase in paired oral-tracheal secretions of adult patients treated with mechanical ventilation. Methods In this descriptive study, paired samples o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 35 publications
(35 reference statements)
0
20
0
1
Order By: Relevance
“…Pepsin can be found in many different tissue samples such as laryngeal mucosa, paranasal sinus mucosa, saliva, middle ear effusion, tracheal secretions and bronchoalveolar lavage fluid (9)(10)(11). It is a large molecule; therefore, it can be easily detected after gastric reflux.…”
mentioning
confidence: 99%
“…Pepsin can be found in many different tissue samples such as laryngeal mucosa, paranasal sinus mucosa, saliva, middle ear effusion, tracheal secretions and bronchoalveolar lavage fluid (9)(10)(11). It is a large molecule; therefore, it can be easily detected after gastric reflux.…”
mentioning
confidence: 99%
“…We have observed that patients may awaken during oral care interventions, but they fall back to sleep immediately after it is done. We have performed this procedure (NO‐ASPIRATE) to obtain specimens in previous studies without any adverse issues, such as gagging or oral trauma (Sole, Bennett, et al., ; Sole, Marano, et al., ; Sole, Middleton, et al., ; Sole, Talbert, et al., ). However, participant response will be observed as part of ongoing monitoring.…”
Section: Discussionmentioning
confidence: 99%
“…Suctioning will be done using standard suction pressures until secretions are no longer audible or visible, for a duration of about 45 s (Chulay & Seckel, ; Sole, Bennett, et al., ). We performed this procedure in previous studies without any adverse issues, such as gagging or oral trauma (Sole, Bennett, et al., ; Sole, Marano, et al., ; Sole, Middleton, et al., ; Sole, Talbert, et al., ). However, participant response will be observed and the procedure will be stopped if intolerance is noted.…”
Section: The Studymentioning
confidence: 99%
“…Alpha‐amylase is an enzyme that initiates the digestive process and is normally present in saliva and oral secretions but not in the lungs. Several researchers have identified α‐amylase in tracheal secretions, indicating microaspiration of oral contents (Abu‐Hasan, Elmallah, Neal, & Brookes, ; Dewavrin et al, ; Filloux et al, ; Qu et al, ; Samanta et al, ; Sole et al, ; Tripathi, Mirant‐Borde, & Lee, ; Weiss, Moazed, DiBardino, Swaroop, & Wunderink, ).…”
Section: Introductionmentioning
confidence: 99%